(untitled) (Research, Society and Development, 2020)
In the quest to present society and the market with a timely alternative of fast and healthy food, this work aimed to prepare artisanal hamburgers with full use of cashew. The preparation of the cashew burger consisted of two formulations, one based on juice (F1) and the other based on fiber (F2). The formulations had the following ingredients: cashew fiber or cashew juice, ground beef, olive oil, textured protein, water, salt, garlic and pepper. Posteriorly, sensory analysis and purchase intent were carried out, with the participation of 54 untrained judges, using the Hedonic Scale as an assessment tool. According to the analysis data, the “color attribute” associated with the average of 6.83 (F1) and 6.72 (F2), the “flavor attribute” 6.97 (F1) and 6.87 (F2) and the “texture attribute” 6.35 (F1) and 6.56 (F2). Finally, the Global Average was 7.27 (F1) and 7.12 (F2) and the purchase intention was “liked it very" for F1 and “liked it very much". Thus, there was a small preference for hamburgers made with cashew juice over those made with fiber.